ANALISIS PENGARUH VARIASI JENIS BAHAN PENGIKAT TERHADAP PERMEABILITAS PASIR CETAK PADA PENGECORAN LOGAM - Tisya Pramesta Ramadhani; Farizi Rachman; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
The results of field observations and reports on the production and quality control of PT. Aneka Adhilogam Karya in 2021, show that the percentage of reject product decrease by 0.23% and company’s quality target decrease by 0.5% from the previous year, it can be concluded that every year the company try to reduce the percentage of reject products which are suspected to be caused by problems in the composition of the molding sand. It was found that the moisture content of the molding sand exceed the normal limit of 11,2%, so that the reject product was suspected to be caused by problems in the composition of the molding sand. Research on the correct composition of molding sand between the composition of sand and binder is needed to improve the quality of casting results. This research was carried out using an experimental method and then comparing the permeability of molding sand and casting results from two types of addition of binders, namely bentonite and molasses. Variations in the composition used are 1%, 3%, and 5%. The results of this study obtained a recommendation for the composition of molding sand that has the highest permeability and produces a product with the least quantity of defects is molding sand with the addition of 5% molasses binder, with a permeability value of 53.50±0.50 cm3/minute and a defect area of 11.97%.